Peningkatan Keterampilan Proses Sains Menggunakan Model Inkuiri Terbimbing dan Performance Assesment pada Siswa XI IPA 1 SMA Kristen 1 Salatiga Tahun Ajaran 2016/2017 - Siti Mayang Mangurai (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
This research aims to understand the increase in skill the process of science students with a guided inquiry model and performance assessment and the implementation of guided inquiry model and performance assessment to students of class XI IPA Christian High School 1 Salatiga . Skills of the research process are studied consisting of observing, hypothesizing, questioning, applying concepts, communicating, and practicing with minimum criteria for psychomotor criteria for 73. The type of research used is classroom action research with data triangulation research technique, in the form of questionnaire instrument, interview sheet, observation sheet, student performance assessment result, and supporting data in the form of documentation. The results showed that the results of the students' science process skills experienced an increase in each cycle. In the first cycle the percentage of science-process skills acquired was 63%. The second cycle percentage increased by 3% to 66%, and the third cycle became 78%. The percentage earned is included in either category. The data is supported with the result of the percentage of observation sheet of learning implementation that is 15% in cycle I, 16% in cycle II, and 20% in cycle III. Student learning outcomes also increased from 77% in cycle I to 87% in cycle II and III. Student's science process skills can be developed using guided inquiry learning model with performance assessment. Guided inquiry models also familiarize students to play an active role in all learning activities and practicum conducted by students, so that students not only understand the material but also skillfully using laboratory tools..